Performance analysis of solar assisted heat pump coupled with build-in PCM heat storage based on PV/T panel. (February 2020) - Yao, Jian; Xu, Hui; Dai, Yanjun; Huang, Mingjun
Highlights: A solar PV/T heat pump is proposed for residential heating in high latitude area. Design of build-in PCM heat storage unit is proposed and simulated. The overall efficiency of this solar PV/T heat pump system can reach above 75%. Abstract: PV/T (photovoltaic/thermal) technology is a combination of PV module (photovoltaic utilization) and collector (photothermal utilization), which can improve the comprehensive utilization efficiency of solar energy and has a broad application prospect. In this paper, PV/T module is coupled with heat pump evaporator to form a direct-expansion solar PV/T heat pump which is suitable for heat application in high latitude area. To achieve stable residential heating, a solar PV/T heat pump system coupled with build-in PCM (phase change material) heat storage is therefore proposed and simulated. Meanwhile, the mathematical model of solar PV/T heat pump coupled with build-in PCM heat storage system is established and verified. The simulation results show that the temperature of underfloor heating which using build-in PCM heat storage can reach 22–31 °C after 39 h when the circulating water is 40 °C. Moreover, the heating COP (Coefficient of Performance) increases with the increase of solar radiation, ambient temperature and area of PV/T collector, and decrease of wind speed, respectively. A 20 m 2 PV/T panel module can output 21.4% of the electricity to power grid when the solar radiation intensity is 600 W/m 2 and meet the heat demand of a 100 m 2 room while maintain the operation of the system. Meanwhile, the heating COP can reach 5.79 which is 70% higher than the conventional air conditioning system and the electrical, thermal, overall efficiencies are 17.77%, 55.76% and 75.49%, respectively.